The effects of undercut geometry on the static stress concentration factor of welds - KURTULMUŞ, MEMDUH (ICE PUBLISHING, 2021)
Undercutting is a welding defect that appears as a groove in the base metal directly along the edges of the weld metal. It is inevitable in fillet and butt joints if improper welding parameters are used in the operation. It is a discontinuity in the welding that produces stress concentration and lowers the strength of the weld. The stress concentration factor of an undercut is due to the reinforcement angle, undercut width, undercut depth and undercut root radius. In this study, 20 mm thick mild steel plates were welded by automatic gas metal arc welding with the carbon dioxide (CO2) shielding gas process. A single-V butt joint was obtained after welding. Before welding, 30 degrees groove angles were obtained by milling on the longitudinal side of each workpiece. Two plates were welded with several passes. After welding, the weldment was tested with a radiographic non-destructive testing process. A defect-free weldment was obtained. Then, standard tensile test samples were machined from the weldment. A groove was drilled in the heat-affected zone, adjacent to the weld metal boundary on every tensile test sample. Each groove resembled an undercut. The length, root radius and depth of grooves were varied. Then, the samples were broken on a tensile test machine. From the test results, the static stress concentration factor of each groove was calculated. The effects of groove geometry on stress concentration factors were determined.
Keywords: material processing; material properties; mechanical properties; ARC; GAS